Nano-crystalline aluminum-containing hydroxyapatite based bioceramics: synthesis and characterization - Kaygili, O.; Tatar, C.; Yakuphanoğlu, Fahrettin; Keser, S. (Springer, 2013)
The hydroxyapatite and hydroxyapatite-based bioceramics with high Al contents were synthesized using sol-gel method, and their characterization was carried out by X-ray diffraction, Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy. With the increase of Al content, the crystallinity is dramatically decreased, and the phase structure belonging to hydroxyapatite was transformed into the new phases, including aluminum calcium phosphate and/or aluminum phosphate. The average crystallite size of the bioceramic samples was found to be in the range of 10-50 nm. FTIR spectroscopy results verified the presence of various and groups in the samples. The density value of the samples significantly increased with the addition of Al. It is evaluated that hydroxyapatite bioceramic can be converted to new bioceramics with high Al contents.
Keywords: Hydroxyapatite; Sol-gel method; Crystal structure